Me While I am Learning Mathematics: Reflections to Elementary School Students’ Drawings - Turgut, Sedat; Gülşen Turgut, İlknur (International Electronic Journal of Elementary Education, 2020)
Each child will not become senior mathematicians in the future but all children have the right to get learning opportunities which he/she can develop his/her mathematical understanding at school. The success of children in mathematics is closely related to how they are taught mathematics. At this point, the role of teaching mathematics stands out in elementary school since they first encounter mathematics as a subject. Elementary school is the place where students first experience success or failure in mathematics. Therefore, the fundamentals of students' tendencies towards mathematics which will set and affect their future learning life are also laid here. The present study aims to examine the perceptions of elementary school students towards learning mathematics by means of their drawings. Drawings are tools for children to express themselves; they provide information about students' drawings on their classes and their understanding of teaching. In this context, based on the experiences of elementary school students, the phenomenon of learning mathematics was aimed to be defined from their perspective. This research employed phenomenology as a qualitative research design. The study group of the research consisted of 326 elementary school students. The data were collected through the drawings of students on the subject of "me while I am learning mathematics". Content analysis was used in the analysis of the data. According to the research results, it is seen that the math learning environment is usually classroom; people in the learning environment are usually teacher and student(s); materials in the learning environment are general items in the classroom environment; symbols in the learning environment are usually numeral-number-four operation symbols; learning mathematics is usually happy-enjoyable-fun and the process of learning mathematics is usually to do arithmetic.